Signal processing for direction finding and range determining to small UAVs in the optical and infrared ranges - Корытцев, И.В.; Шейко, С.А.; Карташов, В.М.; Зубков, О.В.; Олейников, В.Н.; Бабкин, С.И.; Селезнев, И.С. (Radiotekhnika, 2020)
Detection and assessment of UAV coordinates is critical to protect against their unauthorized use in protected areas. The paper considers the problem of choosing the algorithm and parameters of stereo pair video processing in the visible, near-infrared and far-infrared ranges for reliable determination of small UAVs coordinates, further tracking of them and evaluation of UAVs motion parameters. Theoretical analysis of the optical method possibilities for two-channel stereo-video observation is carried out. The paper presents the results of field experiments aimed to determine the coordinates of a small UAV DJI Phantom 4 using a stereo-video observation system based on IP cameras. The external and internal parameters of the stereo-video observation system were calibrated taking into account the nonlinear distortions of the lenses. The cameras were calibrated in OpenCV using a function based on Zhang and Bouguet methods. The theoretical and practical errors in measuring the range to test objects at their different positions were determined. An algorithm for image processing of a stereo-video observation system for detection, recognition and measurement of UAV coordinates is described. The results of measurements of UAV coordinates for two test flights are presented. The measurement of the true coordinates of the UAV was carried out according to the data of the onboard GPS receiver. The results of measuring the azimuth and elevation of the UAV by the stereo-video observation system were matched with the data of the GPS receiver. This fact can be explained by high resolution of the cameras and the precise calibration of their internal parameters. The root-mean-square relative error in measuring the range was about 10%. Ways for improving the accuracy of UAV stereo-video observation systems are shown.